Ideological Tensions in Education Policy Networks: An Analysis of the Policy Innovators in Education Network in the United States - Joseph Ferrare; Laura Carter-Stone; Sarah Galey-Horn (FahrenHouse, 2021)
Previous research has illustrated that advocacy organizations play a crucial role in education policy networks by communicating educational reform agendas to public and private stakeholders. In the United States, an inter-state consortium of these advocacy organizations has formed their own network. The Policy Innovators in Education (PIE) network is a formal, centrally coordinated policy network that connects state-level advocacy organizations to one another and to national advocacy organizations, think tanks, and philanthropic foundations. Despite more than doubling in size since 2016, little is known about the policy preferences of PIE members. In this paper, we use social network analysis to identify and describe the ideological dimensions of advocacy that structure the PIE Network and to examine how these ideological dimensions have changed as the network has expanded. We find that the central areas of emphasis among these organizations have coalesced around neoliberal ideologies that promote accountability and standards. However, there is an underlying tension within the network that unfolds along two dimensions. On the one hand, preferences for choice and autonomy (e.g., charters, general choice, and autonomy & deregulation) are contrasted to those favoring equitable funding for low-income schools and early childhood education. On the other hand, members emphasize policies involving factors internal to schools (student interventions, leadership standards and accountability) to those external to schools (e.g., familial support, funding-based equity). These tensions within the network have grown more pronounced over time as the network has expanded to include new members with a more ideological narrow set of market-based policy preferences.